2023
DOI: 10.1177/00110000231159316
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor Cultural Humility and Supervisee Nondisclosure: The Supervisory Working Alliance Matters

Abstract: Given that at least half of supervisees (therapist trainees) never have their clinical work monitored or observed, supervisees who withhold salient information in clinical supervision compromise supervisors’ ability to monitor client welfare and promote supervisees’ professional development. Attempting to further understand the factors explaining supervisee nondisclosure, we tested the supervisory working alliance as a mediator of the hypothesized inverse relations of cultural humility and collaborative superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…They found supervisor cultural humility regarding supervisees' (but not clients') cultural identity was significantly associated with supervisees' satisfaction with supervision, underscoring the complex nature of "layered cultural interactions" in supervision. Additionally, Ertl et al (2023) found supervisee perceptions of supervisor cultural humility to be inversely related to supervisee nondisclosure in supervision, with SWA mediating this relationship.…”
Section: Supervisor Cultural Humilitymentioning
confidence: 92%
“…They found supervisor cultural humility regarding supervisees' (but not clients') cultural identity was significantly associated with supervisees' satisfaction with supervision, underscoring the complex nature of "layered cultural interactions" in supervision. Additionally, Ertl et al (2023) found supervisee perceptions of supervisor cultural humility to be inversely related to supervisee nondisclosure in supervision, with SWA mediating this relationship.…”
Section: Supervisor Cultural Humilitymentioning
confidence: 92%
“…Trainees report increased levels of self-efficacy and confidence in the clinical services they provide when their supervisors can skillfully discuss race and culture in supervision (e.g., Constantine, 2001; Kissil et al, 2013). Trainees are also more willing to disclose needed clinical care details and ask key treatment questions, which may enhance the overall efficacy of supervision (Ertl, Ellis & Peterson, 2023). In addition, trainees report a stronger supervisory working alliance and overall, more positive attitudes toward their clinical professional development and training (e.g., Crockett & Hays, 2015).…”
Section: Benefits Of Multiculturally Competent Supervisionmentioning
confidence: 99%
“…To establish the most robust evidence, research can be conducted under a host of conditions: diverse clinical training contexts (e.g., university counseling centers, mental health consortiums), supervisees at varying levels of training, supervisors of varying therapeutic orientations, and supervision dyads of varying racial and cultural compositions. Recent studies examining the harmful supervisee experiences and inadequate supervisory feedback (Hutman et al, 2023;Ladany et al, 2013) and promoting supervisor cultural humility, supervisory working alliance, and collaboration (Ertl et al, 2023;Upshaw et al, 2020) suggest new avenues to use the tool in research. A far-reaching research agenda would attempt to establish the linkage of supervisees' development of MCC to their facilitation as therapists of therapeutic outcomes.…”
Section: Future Researchmentioning
confidence: 99%